1912 Ky. Acts 593, Regulate Storage of Explosives and Provide Against Fires, § 17. - (:unkn) unknown (General Publisher, 1912)
To regulate the storage of gunpowder, rosin, tar, pitch, cotton, oil and all other explosives and combustible material, and to appoint some suitable person or persons, at seasonable times, to enter and examine such houses as they may designate, in order to ascertain whether any of such houses are in a dangerous condition with reference to fires, and to cause such as are in a dangerous condition to be immediately put in safe order and condition.
--
Keywords: GUN POWDER STORAGE